Răspunsuri

Cel mai inteligent răspuns!
2014-05-04T16:53:04+03:00
E doar pur calcul. 

a) 5(3x-2)+3x-6(8x-13)=16(9-2x)-78
15x-10+3x-48x+78 = 144 - 32x - 78
-30x + 68 = 66 - 32x
2x = -2 => x= -1

b) 2(3x+4) -5(2x-3) - 2 = 7(2x-4) +2(8-5x)+3x
6x+8 - 10x +15 -2 = 14x - 28 + 16 - 10x +3x
-4x +21 = 7x - 12
33 = 11 x => x=3

c)2(3x-4)+5(6x-7)-3x = 9(x+10)+11(x+12)+8
6x-8 + 30x - 35 - 3x = 9x+90 + 11x+132+8
33x - 43 = 20 x + 230
13x = 273 => x= 21
14 4 14
2014-05-04T16:56:29+03:00
15x-10 +3x-48x+78=144-32x-78
-30+68=-32x+66/+32x
2x+68=66/-68
2x=-2/:2
x=-1
b)6x+8-10x+15-2=14x-28+16-10x+3x
-4x+21=7x-12/-7x
3x+21=-12/-21
3x=-33/:3
x=-11
c)6x-8+30x-35-3x=9x+90+11x+132+8
33x-43=20x+230/-20x
13x-43=230/+43
13x=273/:13
x=21
7 3 7